State-of-the-Art Review: Anatomical and Imaging Considerations During Transcatheter Tricuspid Valve Repair Using an Annuloplasty Approach - Wunderlich, Nina C.; Landendinger, Melanie; Arnold, Martin; Achenbach, Stephan; Swaans, Martin J.; Siegel, Robert J.; Ho, Siew Yen (Frontiers in Cardiovascular Medicine, 2021)
Transcatheter techniques for the treatment of tricuspid regurgitation (TR) are being more frequently used and several new devices are in development. Since 90% of patients with TR have secondary TR, catheter based systems which reduce the dilated tricuspid annulus area are of particular interest. In order to perform an annuloplasty procedure effectively and safely, knowledge about the anatomy of the tricuspid valve apparatus and especially of the annulus in relation to the important neighboring structures such as the aortic root, the RCA, the electrical pathways and the CS is fundamental. In addition, comprehensive understanding of the device itself, the delivery system, its maneuverability and the individual procedural steps is required. Furthermore, the use of multi-modality imaging is important. For each step of the procedure the appropriate imaging modality as well as the optimal; imaging planes are crucial to provide the necessary information to best guide the individual procedural step.